Remarks by World Bank Group President David Malpass at the 2022 Nordic Baltic Governors Meeting - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass at the 2022 Nordic Baltic Governors Meeting on June 9, 2022. He spoke about the following: war in Ukraine; the World Bank Group is responding, with increased financial support to FCV countries, and with more staff on the ground. Addressing the challenges of fragility, conflict and violence requires strengthened international cooperation and deeper collaboration with governments, with partners such as the UN, with civil society, and the affected populations themselves, and climate action.